2021
DOI: 10.1038/s41598-021-93663-1
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 4 mediates adaptation of human glioblastoma cells to hypoxia and temozolomide

Abstract: The integrated stress response (ISR) is a central cellular adaptive program that is activated by diverse stressors including ER stress, hypoxia and nutrient deprivation to orchestrate responses via activating transcription factor 4 (ATF4). We hypothesized that ATF4 is essential for the adaptation of human glioblastoma (GB) cells to the conditions of the tumor microenvironment and is contributing to therapy resistance against chemotherapy. ATF4 induction in GB cells was modulated pharmacologically and genetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…We found that efficient cardiac specification requires the tryptophanyl‐tRNA synthetase WARS1, a conserved transcriptional target of ATF4 also identified in mouse fibroblasts [ 55 ] and human glioblastoma cells. [ 56 ] Aminoacyl‐tRNA synthetases (ARSs) are essential enzymes for protein synthesis [ 57 ] and have not been previously implicated in ESC biology and heart development. ARSs ligate amino acids to their corresponding tRNAs to initiate protein synthesis in a high‐fidelity manner, with one for each amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…We found that efficient cardiac specification requires the tryptophanyl‐tRNA synthetase WARS1, a conserved transcriptional target of ATF4 also identified in mouse fibroblasts [ 55 ] and human glioblastoma cells. [ 56 ] Aminoacyl‐tRNA synthetases (ARSs) are essential enzymes for protein synthesis [ 57 ] and have not been previously implicated in ESC biology and heart development. ARSs ligate amino acids to their corresponding tRNAs to initiate protein synthesis in a high‐fidelity manner, with one for each amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral outcomes are a key functional measure of underlying improvements in molecular and cellular function, which often impact central regulatory pathways. Previously, ISRIB has been shown to improve cognitive function in brain injury (Chang et al, 2021; Chou et al, 2017), cancer (Lorenz et al, 2021), neuropsychiatric disorders (Kabir et al, 2017), neurodegenerative disorders (Oliveira et al, 2021; Wong et al, 2018; Xu et al, 2021), and even healthy cognition (Sidrauski et al, 2013). Our study demonstrated the beneficial effects of ISRIB in a mouse model of FXS, which in combination with recent studies showing the impact of ISRIB treatment in models of Down syndrome (Zhu et al, 2019) and MEHMO (Mental retardation, Epileptic seizures, Hypogonadism and Hypogenitalism, Microcephaly, and Obesity), a rare X-linked disorder (Young-Baird et al, 2020), expands its therapeutic potential to neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia was induced with incubation in GasPak pouches for anaerobic culture (Becton-Dickinson, Heidelberg, Germany) as previously described 23,29,26 . Experiments in hypoxia (0.1% O 2 ) or normoxia (21% O 2 ) were performed in serum-free DMEM adjusted to 2 mM glucose.…”
Section: Methodsmentioning
confidence: 99%
“…The STR profile of LNT-229 cells matched with the known profile for LN-229, which only differ in their p53 status 25 . A STR profile of G55T2 cells has not been deposited in databases yet 26 .…”
Section: Reagents Cell Lines and Culture Conditionsmentioning
confidence: 99%